2008
DOI: 10.1002/jnr.21892
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase‐B activity is not involved in the neuroinflammatory response elicited by a focal freeze brain injury

Abstract: Cryolesion of the frontoparietal cortex in mice is a well-described brain injury paradigm that results in increased astrogliosis surrounding the lesion site and is accompanied by a prominent increase in the MAO-B levels in astrocytes. Whether these increased MAO-B levels contribute to cellular damage or modulate reactive astrocytosis remains unclear. MAO-B activity may contribute to cellular damage, since its metabolism products are highly toxic to the cells. Additionally, it has been suggested that MAO-B inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It appears most of the toxicity Monoamine oxidase- β (MAO- β), a mitochondrial enzyme which metabolizes/inhibits dopamine neurotransmitters has been reported to enhance the production of ROS culminating in cell senescence (Maggiorani et al, 2017). Though there exist some opposing views (Damier et al, 1996; Sanz et al, 2009), our study tends to conform with the former. In this study, it was observed that MAO-B was expressed majorly in the synaptic cleft.…”
Section: Discussionmentioning
confidence: 51%
“…It appears most of the toxicity Monoamine oxidase- β (MAO- β), a mitochondrial enzyme which metabolizes/inhibits dopamine neurotransmitters has been reported to enhance the production of ROS culminating in cell senescence (Maggiorani et al, 2017). Though there exist some opposing views (Damier et al, 1996; Sanz et al, 2009), our study tends to conform with the former. In this study, it was observed that MAO-B was expressed majorly in the synaptic cleft.…”
Section: Discussionmentioning
confidence: 51%
“…Deletion of the MAOB gene was nonprotectivein fact, detrimentalin a mouse MCAO model; additional evidence has been obtained using a cryolesion induced model of brain injury. While reactive astrocytosis has been observed along with a prominent increase in MAOB expression, its selective inhibition had no effect on the expression of cell death and inflammation-related genes, nor did it improve the motor impairment of cryolesioned mice . The observation of upregulated MAOB in the LIV group suggests a neuroprotective role.…”
Section: Resultsmentioning
confidence: 92%
“…While reactive astrocytosis has been observed along with a prominent increase in MAOB expression, its selective inhibition had no effect on the expression of cell death and inflammation-related genes, nor did it improve the motor impairment of cryolesioned mice. 118 The observation of upregulated MAOB in the LIV group suggests a neuroprotective role. The giant phosphoprotein AHNAK is expressed in several cell types, including reactive astrocytes, and implicated in a variety of cellular processes.…”
Section: Journal Of Proteome Researchmentioning
confidence: 97%